2008
DOI: 10.1583/07-2190.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Arterial Closure Devices in Antegrade and Retrograde Punctures

Abstract: Angio-Seal had a lower rate of primary failure than Perclose in antegrade puncture closures. We believe this reinforces the need for larger studies to compare closure devices in antegrade punctures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…While several clinical studies reported device success rates ranging from 90% to 100% which is similar to other devices. 22,48,[58][59][60][61][62] Device failure, while uncommon, has been attributed to suture breakage or failure to create a secured knot. If the Perclose device fails, MC can achieve hemostasis.…”
Section: Clinical Experience With Vascular Closure Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…While several clinical studies reported device success rates ranging from 90% to 100% which is similar to other devices. 22,48,[58][59][60][61][62] Device failure, while uncommon, has been attributed to suture breakage or failure to create a secured knot. If the Perclose device fails, MC can achieve hemostasis.…”
Section: Clinical Experience With Vascular Closure Devicesmentioning
confidence: 99%
“…63 Comparative studies between the Perclose device vs manual compression noted a faster time to achieve hemostasis and ambulation when using the Perclose device. 22,48,[58][59][60][61][62] There are multiple small randomized studies comparing Perclose to MC in the setting of diagnostic angiography, PCI, and both. The results are mixed; some favor Perclose with fewer complications 41,52,64,65 and others favor MC.…”
Section: Clinical Experience With Vascular Closure Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Whereas limited data in support of Perclose and StarClose (both from Abbott Vascular, Santa Clara, CA, USA) have been reported, the use of Angio-Seal (St. Jude Medical) has been described in a series of previous reports, suggesting, albeit inconclusively, its feasibility and safety in this setting. [11][12][13] This issue of the Journal reports a compelling single-center cohort study by Lupattelli et al, 14 enrolling 1626 patients undergoing one or more duplex ultrasound-guided antegrade femoral punctures for lower limb revascularization. This registry showed that, in experienced hands, antegrade Angio-Seal deployment can successfully achieve hemostasis in 97.9% of cases, with a 1.1% rate of early complications, a 2.5% rate of 30-day complications, and no later complications associated with the device.…”
Section: Dedicated Closure Devicesmentioning
confidence: 99%
“…Smaller series have examined the efficacy of deployment of such devices, typified here by the Angio-Seal VIP ("V-Twist Integrated Platform"; St. Jude Medical, Minnetonka, MN, USA). However, there are limited published data, with heterogeneity of study parameters, comparing it to manual compression, 1e3 to other VCDs, 4 or simply registries. 5 There is also very limited data so far comparing the efficacy of the Angio-Seal (now used to imply the Angio-Seal VIP throughout) VCD between retrograde and antegrade punctures.…”
Section: Introductionmentioning
confidence: 99%